Will the crisis trigger a revival of the IMF? Note based on remarks prepared for a panel organised by the Per Jacobsson Foundation in Washington, DC, on 12 October 2008 - Jean Pisani-Ferry (Bruegel, 2008)
In this Policy Contribution, Jean Pisani-Ferry, takes a look at the way the IMF his gradually making its come-back from an era of crisis confidence and legitimacy. The author believes the Fund could gain a significant role as the key institution that links macroeconomic and financial developments and draw implications for macrofinancial supervision, relying on others such as the FSF for implementation. He outlines a series of recommendations to reach this objective.
Keywords: 330; Internationales Währungssystem; Internationaler Finanzmarkt; Welt